2006
DOI: 10.1037/0894-4105.20.5.598
|View full text |Cite
|
Sign up to set email alerts
|

Is the right hemisphere involved in idiom comprehension? A neuropsychological study.

Abstract: Nonambiguous idiom comprehension was assessed in 15 right brain-damaged (RBD) and 12 left brain-damaged (LBD) aphasic patients by means of a string-to-picture matching task. Idiom comprehension was found to be severely impaired with a bias toward literal interpretation. The RBD patients, though impaired, performed significantly better than LBD patients; their performance was correlated with visuospatial abilities and was significantly affected by lesion site. The results of this study suggest that the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 30 publications
1
28
1
Order By: Relevance
“…These two RHD participants were two of the three RHD participants who performed at chance level in the With respect to the neural processing of idioms, the most accepted view about the hemispheric lateralization of idiom processing is that the RH is responsible for processing idiomatic language (see Van Lancker Sidtis, 2006 for a review). However, recent findings also underline the left-hemisphere's contribution to the processing of idioms (Papagno, Tabossi, Colombo & Zampetti, 2004;Papagno, Curti, Rizzo, Crippa & Colombo, 2006). In the present study, despite the fact that 3/5 RHD patients had low scores in the idiomatic language comprehension screening test (Table 2 -Supplemental Materials), they did not differ from the NC participants on any of the measures of prosodic realization, suggesting that RHD in these individuals did not disrupt the use of prosodic cues during idiom production.…”
Section: Discussioncontrasting
confidence: 43%
“…These two RHD participants were two of the three RHD participants who performed at chance level in the With respect to the neural processing of idioms, the most accepted view about the hemispheric lateralization of idiom processing is that the RH is responsible for processing idiomatic language (see Van Lancker Sidtis, 2006 for a review). However, recent findings also underline the left-hemisphere's contribution to the processing of idioms (Papagno, Tabossi, Colombo & Zampetti, 2004;Papagno, Curti, Rizzo, Crippa & Colombo, 2006). In the present study, despite the fact that 3/5 RHD patients had low scores in the idiomatic language comprehension screening test (Table 2 -Supplemental Materials), they did not differ from the NC participants on any of the measures of prosodic realization, suggesting that RHD in these individuals did not disrupt the use of prosodic cues during idiom production.…”
Section: Discussioncontrasting
confidence: 43%
“…Various models have also been proposed to explain how these expressions are mentally represented and processed (Cutting & Bock, 1997;Sprenger et al, 2006;Tabossi, Fanari, & Wolf, 2009;Tabossi, Wolf, & Koterle, 2009). Also, interesting research is conducted on how children acquire the ability to use idiomatic expressions (Ackerman, 1982;Cacciari & Levorato, 1989;Gibbs, 1987Gibbs, , 1991Levorato & Cacciari, 1995;Levorato, Nesi, & Cacciari, 2004), how idiom knowledge and processing are disturbed in aphasic patients (Hillert, 2004;Papagno, Curti, Rizzo, Crippa, & Colombo, 2006;Papagno, Tabossi, Colombo, & Zampetti, 2004), and what structures in the brain are responsible for the processing of idioms and other types of figurative language (Sidtis Van Lacker, 2006).…”
mentioning
confidence: 99%
“…Brownell et al, 1984Brownell et al, , 1990Kempler et al, 1999;Champagne et al, 2004;Rinaldi et al, 2004) confirmed the presence of a defect of metaphorical language in RBD patients, and other authors (e.g. Tompkins, 1990;Tompkins et al, 1992;Giora et al, 2000;Gagnon et al, 2003;Klepousniotou and Baum, 2005;Papagno et al, 2006) found metaphorical language to be equally impaired after RH or LH injury, thus failing to support the hypothesis of a specific contribution of the RH to the processing of metaphorical meaning of words. Essential data about these clinical investigations (subjects, methodology and results) are reported in table I.…”
Section: The Right Hemisphere Metaphorical Language Hypothesismentioning
confidence: 84%